The Czech jewishness of Professor Jiří Franěk, Outstanding Personality in Prague’s Scientific and Cultural Life - Soukupová, Blanka; Fraňková, Zdeňka; Dvořáková, Věra (Lidé města, 2008)
Jiří Franěk (Frischmann) (Nov. 24, 1922, Vysoké Mýto – December 30, 2007, Prague) – Charles University professor, leading Czech literary scholar, Russian studies specialist, publisher of literature and professional books, and the greatest expert on the works of Bohumil Mathesius – can be considered from various angles. In the English-German mutation of the journal Urban People, we will concentrate on his relation to the Jewish minority, with whom his fate was joined. It is in accordance with the main theoretical idea of this journal, a theme which accentuates the mutual bond between the character of a city and its inhabitants, and with the effort of postmodern anthropology to analyze the complex structure of collective and individual identity.